2008
DOI: 10.1016/j.icarus.2007.09.018
|View full text |Cite
|
Sign up to set email alerts
|

The opacity of grains in protoplanetary atmospheres

Abstract: We have computed the size distribution of silicate grains in the outer radiative region of the envelope of a protoplanet evolving according to the scenario of Pollack et al. (1996). Our computation includes grain growth due to Brownian motion and overtake of smaller grains by larger ones. We also include the input of new grains due to the breakup of planetesimals in the atmosphere. We follow the procedure of Podolak (2003), but have speeded it up significantly. This allows us to test the sensitivity of the cod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
107
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(121 citation statements)
references
References 14 publications
14
107
0
Order By: Relevance
“…In contrast, outside 4.5×10 11 cm, the opacity increases with f D/G,disk (variation by a factor of ∼20). This is again a clear sign that in the outermost layers, Brownian coagulation is important (Movshovitz & Podolak 2008).…”
Section: Impact Of the Dust-to-gas Ratio In The Diskmentioning
confidence: 83%
See 4 more Smart Citations
“…In contrast, outside 4.5×10 11 cm, the opacity increases with f D/G,disk (variation by a factor of ∼20). This is again a clear sign that in the outermost layers, Brownian coagulation is important (Movshovitz & Podolak 2008).…”
Section: Impact Of the Dust-to-gas Ratio In The Diskmentioning
confidence: 83%
“…By construction, in all three regimes, the growth and settling timescales are the same. Movshovitz & Podolak (2008) found that the grain evolution approaches a steady state in only 100 yrs, and that after 1000 yrs, the steady state is fully established. Similarly short timescales are also found in the analytical model.…”
Section: Timescalesmentioning
confidence: 99%
See 3 more Smart Citations